2015
DOI: 10.1021/acs.langmuir.5b00039
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Study of Emulsions Stabilized by Soft and Rigid Particles

Abstract: Two distinct uniform hybrid particles, with similar hydrodynamic diameters and comparable zeta potentials, were prepared by copolymerizing N-isopropyl acrylamide (NIPAM) and styrene.These particles differed in their styrene to NIPAM (S/N) ratios of 1 and 8, and were referred to as S/N 1 and S/N 8. Particle S/N 1 exhibited typical behavior of soft particles, i.e., the particles shrank in bulk aqueous solutions when the temperature was increased. As a result, S/N 1 particles were interfacially active. In contras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 46 publications
2
39
0
Order By: Relevance
“…Previous research confirmed that coalescence is feasible when the interfacial shear yield strength of the particle layer is exceeded. 20,27,40 In an attempt to understand why bubble coalescence was possible when the particle-laden interfaces were elastically dominant, we considered the relationship between the compressive stress acting on the thin liquid film separating two bubbles intimately in contact, 10 and the yield stress of the particle-laden interface. Assuming an average bubble diameter (2R) of 400 µm and the surface tensions ( ) taken from the data presented in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research confirmed that coalescence is feasible when the interfacial shear yield strength of the particle layer is exceeded. 20,27,40 In an attempt to understand why bubble coalescence was possible when the particle-laden interfaces were elastically dominant, we considered the relationship between the compressive stress acting on the thin liquid film separating two bubbles intimately in contact, 10 and the yield stress of the particle-laden interface. Assuming an average bubble diameter (2R) of 400 µm and the surface tensions ( ) taken from the data presented in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Eventually a critical strain is surpassed when the film transitions from solid-like (G' > G") to liquid-like (G' < G") response. 20,27 In an oscillation stress ramp test (data not shown) the yield point ( ) of the three particle layers, identified as the crossover in G' and G" particle spreading concentration = 0.5 wt%; spreading volume = 10 L.…”
Section: Interfacial Rheology Of Deposited Particle Layersmentioning
confidence: 99%
“…The way particles adsorb and arrange at the interface directly impacts the emulsion stability. Li et al [37] noticed that by varying the poly(N-isopropyl acrylamide)-styrene microgels softness, the softer ones allowed better emulsification and better stability than the rigid ones. Moreover, these microgel-stabilized emulsions can be produced using the limited coalescence principle, in the same way as rigid particle-stabilized emulsions [167].…”
Section: Equationmentioning
confidence: 99%
“…Long times for adsorption are common for complex proteins, 34 but also for soft particles that are surface active. 35,36 As indicated earlier, the thylakoid fragments as expected to consist of membrane proteins covered by lipids, which can provide a stable conformation to the protein/lipid complexes and render a soft particle that adsorbs to the interface.…”
Section: Dynamic Interfacial Tensionmentioning
confidence: 91%